Perbandingan Karakteristik Sifat Kimia Tanah Sawah dengan Pemberian POC Marolis dan Kompos IPM Malang Di Kedungkandang, Malang - Iradat Tito , Sama? ; Rahardjo , Poegoeh Prasetyo (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2018)
The purpose of this study was to determine the comparison of the characteristics of soil chemical properties with POC Marolis, mahogany leaf compost IPM Malang and its combination in Tlogowaru, Kedungkandang, Malang. This study lasted for 100 days (one planting season) in rice fields inpari 30 ciherang varieties. Data retrieval method with observation method which includes (1) phase before planting, (2) vegetative phase and (3) generative phase. Soil sampling was taken with a depth of 30 cm. Soil sampling was tested at the Laboratory of Soil Chemistry, Faculty of Agriculture, Brawijaya University, Malang. Parameters tested include pH, Organic C, total N, C / N, P Bray ratio, base cations (K, Na, Ca, Mg, KTK, KB). Based on the results of the study it can be concluded that the best treatment of the characteristics of the chemical properties of paddy soil is owned by a combination of POC and compost which has a relatively acidic soil pH when the vegetative and generative phases, organic C and N Total are classified as starting before planting up to the generative phase, K Base Cation is classified as moderate from the vegetative to generative phase, Na Base Cation increases to moderate when the generative phase, Ca starts before planting to the high generative phase, high KTK starts from planting to generative conditions.